Treibhaus 3 : 17 Künstler aus Düsseldorf, Köln, Hamburg : Dokumentation der Ausstellung. - Kunstmuseum Düsseldorf (Düsseldorf : Kunstmuseum Düsseldorf, 1985)
Bordanowicz, Jürgen ; Hanousek, Michael ; Hashimoto, Sohei ; Hellinger, Horst ; Herold, Georg ; Jakubaschke, Sigrun ; Kleinlein, Gisela ; Knaust, Rainer ; Lambertin, Theo ; Lepper, Gereon ; Mademann, Doris ; Näher, Christa ; Reinecke, Chris ; Sugai, Nobuko ; Techler, Andreas ; van Well, Raimund ; Wolf, Josef
Treibhaus 3 : 17 Künstler aus Düsseldorf, Köln, Hamburg, Kunstmuseum Düsseldorf, 28. September bis 3. November 1985
boek